2014
DOI: 10.1128/aem.01604-14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Populus Genotype on Gene Expression by the Wood Decay Fungus Phanerochaete chrysosporium

Abstract: fWe examined gene expression patterns in the lignin-degrading fungus Phanerochaete chrysosporium when it colonizes hybrid poplar (Populus alba ؋ tremula) and syringyl (S)-rich transgenic derivatives. A combination of microarrays and liquid chromatography-tandem mass spectrometry (LC-MS/MS) allowed detection of a total of 9,959 transcripts and 793 proteins. Comparisons of P. chrysosporium transcript abundance in medium containing poplar or glucose as a sole carbon source showed 113 regulated genes, 11 of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
(66 reference statements)
0
29
1
Order By: Relevance
“…To date, genome-wide transcriptome studies of gene expression in P. chrysosporium and P. placenta have been conducted only after incubation for a single, predetermined growth period in submerged cultures supplemented with ground wood substrate, glu- cose, or microcrystalline cellulose (17,28,(33)(34)(35)(36)(37). Although these studies have contributed to our understanding of the transcriptional regulation and modulation of gene expression on woody substrates, they bear little resemblance to solid substrates, where accessibility to cell wall polymers likely influences transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genome-wide transcriptome studies of gene expression in P. chrysosporium and P. placenta have been conducted only after incubation for a single, predetermined growth period in submerged cultures supplemented with ground wood substrate, glu- cose, or microcrystalline cellulose (17,28,(33)(34)(35)(36)(37). Although these studies have contributed to our understanding of the transcriptional regulation and modulation of gene expression on woody substrates, they bear little resemblance to solid substrates, where accessibility to cell wall polymers likely influences transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…Initial work in this area employed quantitative reverse transcriptase PCR (RT-PCR) measurements of select transcripts and showed that ligninolytic peroxidases are highly expressed by P. chrysosporium on wood (17), but it did not address the overall coordination of lignin degradation. With the advent of the initial genome assembly and annotations (v1.0 and v2.1) (18), microarray-based transcriptome analysis allowed examination of transcript levels of P. chrysosporium genes during growth on ball-milled wood and in defined growth media (19)(20)(21)(22)(23). This approach provided useful insights but was limited to 10,048 v2.1 targets and complicated by the unpredictable manner in which the fungus responds to unnatural carbon sources in submerged basal salts medium.…”
mentioning
confidence: 99%
“…Genes encoding various CAZymes such as cellobiohydrolases, endoglucanases, β-glucosidase, endoxylanases, endo glucanases and mannases were found to be expressed in control conditions and the same genes were downregulated in oak extractives 25. In 2014, Gaskell et al has performed gene expression studies on P. chrysosporium to understand the influence of Populus genotype (P717, 82 and 64 transgenic lines) on its gene expression (GSE52922) 27. Results from this study showed that genes coding for GH-6 (CBH2), AA-3 (CDH), AA9 (LPMO), GH5 (endoglucanases) were highly upregulated in P717.…”
Section: Resultsmentioning
confidence: 99%
“…Till date there are 6 Microarray, 1 RNA sequencing and 1 Long-SAGE (Serial Analysis for Gene Expression) studies based on P. chrysosporium, out of which we have analyzed the microarray and RNA sequencing studies to understand the cellulolytic and hemicellulolytic degradation mechanisms. Accession IDs of microarray datasets retrieved from NCBI GEO are GSE14734 23, 24, GSE14735 23, 24 GSE54542 25, GSE2794126, GSE52922 27, GSE69008 28 GSE6946129 details of these gene expression datasets were shown in the Table 1.…”
Section: Data Analysis Methodologymentioning
confidence: 99%
See 1 more Smart Citation